Psychosocial and occupational impact assessment due to internet addiction: A critical review - Senthil Vadivel Vadivu (2020)
© 2020 EManuscript Technologies. All rights reserved. The review article of "Psychosocial and Occupational Impact Assessment due to Internet Addiction: A Critical Review" that was scoped by literature review aims to map the relevant articles, literature and the process of summarizing various pieces of evidence for delivery based on a non-empirical design. Data was collected from secondary sources including research articles, international journals, electronic sources, and theories. The results showed data for internet addiction prevalence in global studies and presented the psychosocial and occupational impact assessments due to internet addiction. Based on the results, the researcher suggested developing new assessment and psychometric properties that are appropriate for research of the target and to verify instrument quality in the research.